Izvlečki predavanj / 4. posvet o ohranjanju in trajnostni rabi rastlinskih genskih virov, [19. junij 2018, Hoče] (University of Maribor Press, 2018)
Extracts of lectures / 4th Conference on Conservation and Sustainable Use of Plant Genetic Resources, [19th of June 2018, Hoče]. This publication contains abstracts of contributions presented at the 4th Conference on Conservation and Sustainable Use of Plant Genetic Resources, which was organized by the Faculty of Agriculture and Life Sciences in cooperation with the Ministry of Agriculture, Forestry and Food. The main purposes of the conference, which is organised each year, are to raise public awareness on the importance of conserving plant genetic resources in Slovenia. The conservation of plant genetic resources (PGR) is carried out within the framework of the Plant Gene Bank Public Service (PGBPS), which combines coordinated programs for preservation and study of PGR at the Agricultural Institute of Slovenia in Ljubljana, the Department of Agronomy of the Biotechnical Faculty, in Ljubljana, the Slovenian Institute for Hop Research and Brewing in Žalec and the Faculty of Agriculture and Life Sciences in Maribor. The main topic of this year’s conference was the conservation of the genetic resources of fruit plants and vines in the form of plantations, the discussion on the use of PGR for the creation of a wider range, i.e. local varieties and the presentation of two relevant research projects. The main activities within the European Cooperative Program for Plant Genetic Resources (ECPGR) were presented.